Transcranial direct current stimulation (tDCS) targeting the left inferior frontal gyrus: Effects on creativity across cultures. (4th May 2019) - Ivancovsky, Tal; Kurman, Jenny; Morio, Hiroaki; Shamay-Tsoory, Simone
ABSTRACT: Although evidence points to the existence of cultural differences in creativity, the mechanisms that underlie these differences are largely unknown. The twofold model of creativity posits two recursive stages: a generation phase and an evaluation phase. Considering that recent studies suggest that the left inferior frontal gyrus) L-IFG(may inhibit creativity during the evaluation phase, we hypothesized that manipulating IFG activity would affect participants' level of creativity. We further predicted that the IFG may be "hyperactive" in a culture that typically discourages uniqueness (e.g., Japan) as compared to a Western culture (e.g., Israel); therefore the effect of inhibiting the L-IFG was expected to be higher in Japanese. To support this hypothesis we altered L-IFG activation using tDCS (transcranial direct current stimulation) in 30 Japanese and 30 Israeli participants and examined the effect of anodal and cathodal stimulation on divergent thinking (DT). Regardless of culture, cathodal stimulation increased creativity compared to sham, while anodal stimulation diminished creativity. Although cultural differences were found in DT scores, stimulation had no differential effect between the cultures. Taken together, the results confirm that the L-IFG plays a key role in creativity across cultures. The null findings regarding the expected interaction between stimulation and culture are discussed.